Hydrochemical characterization of an acid mine drainage-affected water reservoir : the Sancho Dam (Huelva, SW Spain) - Cerón, J. C. (2014)
The present study has the following objectives: to discover the relation between variables and the hydrochemical variations related to acid mine drainage in a water reservoir, and to describe horizontal stratification relating to vertical salinity and variations in metals. The information obtained may be used for establishing risk evaluation criteria and to design future remediation strategies, which could be useful for new dams. The hydrochemical characterization was based on a sampling campaign performed in October, 2011. A total of 28 samples, at one-meter-deep intervals, were obtained. The hydrogeochemical study of the polluted reservoir showed that the dilution effect is not sufficient to neutralize Acid Mine Drainage contributions from mining activity. Sampling carried out from the surface water to the deepest points reveals the reservoir stratification, which allows it to be included in the group of monomictic and holomitic lakes.